Algebra and Trigonometry 10th Edition

Published by Cengage Learning
ISBN 10: 9781337271172
ISBN 13: 978-1-33727-117-2

Prerequisites - p.4 - Factoring Polynomials - Exercises - Page 39: 51



Work Step by Step

Use $-x=9x-10x$ $6x^2-x-15=6x^2+9x-10x-15=(3x)2x+(3x)3+(-5)2x+(-5)3=3x(2x+3)+(-5)(2x+3)=(3x-5)(2x+3)$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.